Screening assays for assessing resistance of European larch to larch canker disease - Kügler, Erik (2020)
Larch canker disease caused by the ascomycete fungus Lachnellula willkom-mii has made European larch (Larix decidua) cultivation unprofitable. The pathogen originates from east-Asia and was introduced to Europe in the 18th century and since then has caused large scale damage in European larch plantations and natural forests. A low level of resistance to L. willkommii has been identified in the natural population of European larch, notably from ma-terial sourced from Poland which offers potential for resistance breeding in the future. Screening resistance requires reliable methods to accurately phe-notype trees. The aim of the study was to determine a proper inoculation method that can be used for resistance testing in the field, considering differ-ences in host response based on the inoculum substrate used and the varia-tion in virulence among isolates of the pathogen. In greenhouse experiments, the differences in lesion size (disease severity) on European larch were de-termined three months following inoculation with L. willkommii using two dif-ferent inoculum substrates (agar and wood) colonized by the fungus and five different isolates originating from Sweden and the Czech Republic. Analyses of the disease symptoms demonstrated that agar plug colonized by L. willkommii caused significantly longer lesion lengths than colonized wood chips. No differences in disease severity were found among isolates. The re-sults indicate the importance of inoculum choice and the negligible effect of isolate choice for future screening of resistance in field trials. Future breeding experiments will potentially result in cultivation of L. decidua as a renewed valuable species option for Sweden and northern Europe.